(3QSGdI aj GdfMhs - (3CHhfUQ jhSa Hf Ydj GdaGOGQjs ((3CHhLYaQ CMeO Hf Ydj GdebQF GdHjgbj s)
(3ChdgG (B:s
(3bGd GdaGOGQj(B: (3CMSf eG bjd(B: (3Cf Jbhd aj MO GdGSe cd daX Od Ydi eYfi aj faSg ZjQg, ebJQf HReGf eMUd s
(3BNQgG (B:s
(3hPcQ Cfge CeGdhG CTjGA Ydi ZjQ GdbjGS fMh bhdge LGAfj fGS hGdYLGL hGdMLGL hgPG EfeG LGR dcKQI GdESJYeGd JNajakG dG ZjQ, gPG BNQ GdHGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B122 - (3U(B126s
(3aj GdMO hGdEeGdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B141 s
(3eUOQ GbJfGA GdCUd (B:s
(3EjQGf s
Keywords: (3GdfMhs